Living Sufism in SIHATSU (Silat Hati Suci): Practices and Impact - Alvi Nour Sholihah (Journal Intellectual Sufism Research (JISR), 2022)
This article discusses one of the phenomena in Gresik Regency, precisely in Bunga District, there is an internal martial arts college called Sihatsu in which it only teaches three movements starting with "pengisian" which is different from martial arts schools in general. This study uses a qualitative method with a field research type of phenomenological approach to find elements of living Sufism in this college, namely the Sihatsu college based on the Qadiriyah wan Naqsabandiyah al-Ottoman congregation, this is because the teachers of this college are direct students of Sheikh Uthman al-Ishaqy (mursyid tarekat Qadiriyah Wan Naqsabandiyah in Surabaya). The teachings that are required for students of this college are Riyadhah and Mujahadah bersanad of Sheikh Uthman al-Ishaqy. From Mujahadah and Riyadhah, every student can pour it into medicine by using verses from the Qur'an or commonly known as Sufi Healing .